2018
DOI: 10.1080/17445647.2018.1526718
|View full text |Cite
|
Sign up to set email alerts
|

Flood hazard of major river segments, Benevento Province, Southern Italy

Abstract: On 15 October 2015, a storm-induced flood hit the central sector of Benevento Province (southern Italy) causing two deaths and severe damage to infrastructure, buildings and local agriculture. This area has a long history of similar events and since 1924 its major river segments have been monitored with several hydrometric stations. We used data from two of these stations and a LiDAR derived high-resolution topography to develop a flood hazard map. For map computation, we first derived a flood inundation map f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Recent studies [41] found that the flood covered an overall area of about 30 km 2 of the entire Calore River floodplain and reached a maximum river stage of ∼9.8 m at the Solopaca stream gauge station, located a few tens of kilometers downstream from the study area ( Figure 1). A very similar stage of ∼9.5 m was also estimated in Benevento [41]. As previously stated, an event similar to the flood described in this paper occurred in 1949.…”
Section: The 15 October 2015 Event: a Brief Outlinementioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies [41] found that the flood covered an overall area of about 30 km 2 of the entire Calore River floodplain and reached a maximum river stage of ∼9.8 m at the Solopaca stream gauge station, located a few tens of kilometers downstream from the study area ( Figure 1). A very similar stage of ∼9.5 m was also estimated in Benevento [41]. As previously stated, an event similar to the flood described in this paper occurred in 1949.…”
Section: The 15 October 2015 Event: a Brief Outlinementioning
confidence: 96%
“…In this study, a GIS-based, object-oriented geomorphological map of the Calore River floodplain in the surroundings of Benevento (southern Italy; Figure 1), overflooded by the 15 October 2015 destructive flood [41] is presented. From a geomorphological point of view, in the Benevento basin, at least four orders of land surfaces, interpreted as remnants of depositional glacis [47], shaped in the alluvial and fluviolacustrine deposits described above, whose ages range from Middle Pleistocene to Holocene, are present.…”
Section: Introductionmentioning
confidence: 99%
“…The flooded areas of major river segments of the Calore River were described in a previous mapping study [20]; here, we considered the flooded areas in the entire Benevento province.…”
Section: Effects Of the Stormsmentioning
confidence: 99%
“…The overflow of the Tammaro and Calore rivers damaged Benevento's industrial area, which is downstream and near the confluence of these two rivers. In this area, the water reached an estimated maximum level of 9.5 m [20] and destroyed important local infrastructures and factories ( Figure 9A). Further downstream, some of the most damaged zones include a sector of the historical center of Benevento ( Figure 9B) and the area named "Pantano" (Figure 9C,D), which means swamp-a clear reflection of its history.…”
Section: Floodingmentioning
confidence: 99%
“…Flood hazard and risk evaluations can be completed using the results of deterministic hydrodynamic models that simulate water movement across the floodplain. In the presence of monitoring (fluvial stage or discharge) and topographic data, statistical models associated with GIS processing can provide a basis for such kinds of analyses [6][7][8]. Both deterministic and statistical models need to be calibrated and validated using available flood data in terms of spatial extent, persistence, and frequency.…”
Section: Introductionmentioning
confidence: 99%